Nanoparticles in prosthetic materials: A literature review - B Devi Parameswari; S Dhevishri; R Ranjith; H Annapoorni (Wolters Kluwer Medknow Publications, 2021)
The commonly used prosthodontic materials are resins, ceramics, metals and silicones. A comprehensive review of literature was completed about the incorporation of nanomaterials in prosthetic dentistry using PubMed and Google Scholar databases. This was supplemented with a manual search of selected journals. English language articles in peer- reviewed journals were selected. Current literature reveals that incorporation of nanomaterials has significantly improved the properties of the prosthetic materials within the clinically acceptable ranges. There appears to be a need for a standardization for these in vitro studies carried out to evaluate their physical, mechanical and antimicrobial properties